Shareholders, Strategy and Value Creation: The Case of the IT Sector - Wojciech Muras; Katarzyna Szczepańska-Woszczyna (Routledge, 2024)
The central task of contemporary strategic management is to look for sources of value and to achieve above- average firm performance. The effective implementation of a value creation strategy requires a comprehensive approach, including the creation of a systemic management structure aimed at increasing company value. The concept of value- based management involves consciously inspiring, undertaking, and implementing value- oriented actions. Value creation takes place at all levels of management and in all organisational units of the company; therefore, the implementation of all management functions should be assigned to this goal. Thus, the role of managers is gaining importance, especially those who are capital- linked to companies, who set goals and verify them by means of informed decisions aimed at maximising value in the long term. The book presents a multidimensional analysis of shareholders' impact on company value creation. The authors chose the IT sector as the area of study; this sector, being one in which modern technologies are essential, acquires special significance for the global economy. The book features a review of notions and concepts related to the management of company value and methods of measuring it, the shareholder's impact on the creation of company value, and factors affecting long- term value creation; an analysis of the places of occurrence, power and direction of a shareholder's impact on building the long- term capacity of an IT sector company for creating the value thereof, as well as the conceptualisation and operationalisation of such impact; an analysis of the role of shareholders in IT sector companies, a profile of shareholder competence which makes the role of a shareholder unique to the company and fulfils the “value- creating owner” postulate; an analysis of the role of hired managers cooperating with the shareholders with an indication of the significance of mutual development and the supplementation of one's own skills. The book is dedicated to scientists in the field of strategic management, valuebased management, and leadership; shareholders; students of EMBA and MBA programmes; practitioners in strategic management; and current shareholders of modern technology companies (in particular from the IT sector) and future investors, for all of whom it may offer a valuable outlook on the management principles and practices in the sectors, particularly with respect to the long- term creation of company value.
Keywords: 650; Strategic Management; Value Creation; Shareholders; Shareholder Value Creation; Shareholder Theory; Leadership; Managerial Competencies; IT Sector